Обзор современных методов обработки деталей сложных форм типа моноколесо из монолитной заготовки - Бондарь, Инна Владимировна; Криворучко, Дмитрий Владимирович (НТУ "ХПИ", 2018)
В настоящее время детали машин становятся все более сложными и точными. В этих условиях применение многоосевых станков с ЧПУ является действенным решением поставленных задач, так как различные компоновки этих станков позволяют обрабатывать детали разной серийности, габаритов и конфигураций. В работе представлена классификация деталей, требующих пятиосевой обработки. Рассмотрены особенности и резервы повышения эффективности пятиосевой обработки выделенных типов деталей. Отдельно рассмотрены методы повышения эффективности пятиосевой обработки деталей сложных форм (типа турбинных лопаток, крыльчаток и др.) на всех этапах обработки (черновая обработка; получистовая обработка; чистовая обработка). Выделены моменты, которым следует уделять особое внимание при пятиосевой обработке деталей сложных форм типа моноколесо из монолитной заготовки.

At the present time, the parts of the machines are becoming more complex and precise. This requires the development of new machining technologies. In these conditions, multi-axis CNC machining is one of those technologies. Various configurations of five-axis machines allow processing parts of different series, dimensions and configurations. In spite of the 20-year history of development, this approach still requires increasing efficiency in implementation to modern tasks. This article presents classification of the parts requiring five-axis machining. Three types of parts are identified: prismatic parts; molds, stamps; parts of complex forms. Each of the types of parts requires different approaches to processing, different methods for improving efficiency. The features of processing of parts of complex forms such as blisk are considered separately. In this article methods of increasing the efficiency of five-axis machining of complex parts (such as turbine blades, impellers, etc.) at all stages of processing (roughing, semi-finished processing, finishing) are considered.
Review of modern methods of five-axis machining on CNC milling machines of complex parts such as blisk from monolithic billet
Keywords: вибрация; стратегия обработки; обработка деталей; пресс-форма; определяющее соотношение; ОС; machining strategy; trajectory of machining; vibration